Ink4a and Arf differentially affect cell proliferation and neural stem cell self-renewal in Bmi1-deficient mice - Bruggeman, Sophia W M; Valk-Lingbeek, Merel E; van der Stoop, Petra P M; Jacobs, Jacqueline J L; Kieboom, Karin; Tanger, Ellen; Hulsman, Danielle; Leung, Carly; Arsenijevic, Yvan; Marino, Silvia; van Lohuizen, Maarten (Genes & development, 2005)
The Polycomb group (PcG) gene Bmi1 promotes cell proliferation and stem cell self-renewal by repressing the Ink4a/Arf locus. We used a genetic approach to investigate whether Ink4a or Arf is more critical for relaying Bmi1 function in lymphoid cells, neural progenitors, and neural stem cells. We show that Arf is a general target of Bmi1, however particularly in neural stem cells, derepression of Ink4a contributes to Bmi1(-/-) phenotypes. Additionally, we demonstrate haploinsufficient effects for the Ink4a/Arf locus downstream of Bmi1 in vivo. This suggests differential, cell type-specific roles for Ink4a versus Arf in PcG-mediated (stem) cell cycle control.